Computational Procedure to Replace a Bulky Flywheel by a Controlled Motor and a Smaller Flywheel - Manjusha Viraj Palandurkar; Jayant P Modak; Shrikrishna G Tarnekar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
Process machines with tougher duty cycles are subjected to wide fluctuations in load torque. These often need a bulky flywheel for torque equalization with disadvantages of torsional oscillations. This results into fatigue of mechanical power transmission elements leading subsequently to equipment failure causing prolonged and frequent down time which results into financial losses. A simpler acceptable alternative is proposed in this article. Suitably monitored VVVf drives and low moment of inertia offer a much better alternative, for improving the system behavior drastically. Controlling the power input to the main electric drive with VVVf technique can generate almost matching demand torque characteristics. A much smaller flywheel is able to improve the accuracy to have better torque matching. This paper deals with estimation of necessary moment of inertia of flywheel in view of minimizing the difference in the required demand torque characteristics and the generated supply torque characteristics.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.881